The WID-qEC test: Performance in a hospital-based cohort and feasibility to detect endometrial and cervical cancers - Schreiberhuber, Lena; Herzog, Chiara; Vavourakis, Charlotte D; Redl, Elisa; Kastner, Christine; Jones, Allison; Evans, Iona; Zikan, Michal; Cibula, David; Widschwendter, Peter; Pfau, Karin; Math, Barbara; et al. (International journal of cancer, 2023)
The majority of endometrial and cervical cancers present with abnormal vaginal bleeding but only a small proportion of women suffering from vaginal bleeding actually have such a cancer. A simple, operator-independent and accurate test to correctly identify women presenting with abnormal bleeding as a consequence of endometrial or cervical cancer is urgently required. We have recently developed and validated the WID-qEC test, which assesses DNA methylation of ZSCAN12 and GYPC via real-time PCR, to triage women with symptoms suggestive of endometrial cancer using ThinPrep-based liquid cytology samples. Here, we investigated whether the WID-qEC test can additionally identify women with cervical cancer. Moreover, we evaluate the test's applicability in a SurePath-based hospital-cohort by comparing its ability to detect endometrial and cervical cancer to cytology. In a set of 23 cervical cancer cases and 28 matched controls the receiver operating characteristic (ROC) area under the curve (AUC) is 0.99 (95% confidence interval [CI]: 0.97-1.00) with a sensitivity and specificity of 100% and 92.9%, respectively. Amongst the hospital-cohort (n = 330), the ROC AUC is 0.99 (95% CI: 0.98-1) with a sensitivity and specificity of 100% and 82.5% for the WID-qEC test, respectively, and 33.3% and 96.9% for cytology (considering PAP IV/V as positive). Our data suggest that the WID-qEC test detects both endometrial and cervical cancer with high accuracy.
Keywords: cervical cancer; endometrial cancer; dysplazie děložního hrdla; Sensitivity and Specificity; Papillomavirus Infections; early detection; Uterine Cervical Dysplasia; nádory děložního čípku; studie proveditelnosti; Vaginal Smears; Endometrium; vaginální stěr; DNA methylation; cytodiagnostika; infekce papilomavirem; ženské pohlaví; Humans; endometrium; Uterine Hemorrhage; abnormal vaginal bleeding; senzitivita a specificita; Uterine Cervical Neoplasms; Female; Cytodiagnosis; Feasibility Studies; lidé; děložní krvácení